Are silicate‐rich inclusions in spodumene crystallized aliquots of boundary layer melt?. Issue 4 (11th May 2013) - Anderson, A. J.
Abstract: The constitutional zone refining model for the internal crystallization of granitic pegmatites stipulates that a highly fluxed and incompatible element‐enriched boundary layer melt evolves at the surface of crystal growth fronts in undercooled granitic melts. It has been argued that silicate‐rich inclusions in primary spodumene and petalite from the Tanco pegmatite are the crystallized products of an entrapped boundary layer melt. However, inclusions of identical character and composition to those in primary spodumene are also abundant in the spodumene component of SQI (spodumene + quartz intergrowths) that formed by the isochemical breakdown of petalite. Both textural types of spodumene at Tanco host fluid inclusion assemblages that display highly variable proportions of solid phases (dominantly cookeite, quartz, and zabuyelite) and a low salinity (approximately 6 wt% NaCl equivalent) aqueous fluid. The average major element content of three fluid inclusion assemblages is approximately Li2 O (3 wt%), Al2 O3 (11 wt%), SiO2 (30 wt%), CO2 (3 wt%) and H2 O (53 wt%). The entrapment of these fluid inclusions is temporally and spatially unrelated to the flux‐rich melt that may have developed at the primary crystallization front of the pegmatite. Petrographic evidence and the mineralogical and chemical composition of spodumene‐hosted inclusions suggest that inclusions in spodumene are the products of hydrothermal dissolution of the host and the precipitation of quartz, cookeite, and zabuyelite prior to and during necking. Abstract : Silicate‐rich inclusions in primary spodumene from the Tanco pegmatite, Manitoba, are identical in all respects to inclusions in secondary spodumene that formed by the isochemical breakdown of petalite. Inclusions in both textural types of spodumene trapped a solute‐rich aqueous carbonic fluid after the advance of a primary crystallization front and therefore do not represent the crystallized products of a flux‐rich boundary layer melt. The dominant minerals in the inclusions (i.e., cookeite, quartz and zabuyelite) precipitated following partial dissolution of the host.